(untitled) (REMUNOM, 2025)
Gamification and personalized education have emerged as innovative approaches in the educational landscape, aligned with the demands of the 21st century. Gamification, defined as the application of game elements in non-game contexts, uses scoring systems, rewards, narratives, and immediate feedback to create more engaging and motivating learning experiences. Authors such as Hamari, Koivisto, and Sarsa (2014) highlight that gamification increases students’ intrinsic motivation, especially when aligned with educational objectives. Deci and Ryan’s (2020) Self-Determination Theory reinforces that gamification addresses the basic psychological needs of autonomy, competence, and relatedness, which are essential for student engagement. On the other hand, personalized education adapts teaching to the individual needs of students, allowing each one to learn at their own pace and according to their interests. Howard Gardner (1983), with his Theory of Multiple Intelligences, argues that personalization is crucial to respect different learning styles. Adaptive platforms, such as Khan Academy, exemplify how technology can be used to personalize learning, offering content tailored to the specific needs of each student. However, the implementation of these strategies faces challenges, such as the lack of technological infrastructure, the need for teacher training, and the risk of over-gamification, where students focus more on rewards than on content. Gamification can also contribute to the development of 21st-century skills, such as critical thinking, problem-solving, and collaboration, preparing students for future challenges. In conclusion, gamification and personalized education offer a promising approach to transforming education, making it more dynamic, inclusive, and effective. However, their implementation requires careful planning, investments in infrastructure, and continuous evaluation to ensure that educational objectives are achieved.